Perancangan Sistem Informasi Pemerintahan Berbasis Web Studi Kasus Kantor Kelurahan Sumur Batu - Yusriel Arief Ferdiyanto (Paradigma, 2019)
Nowadays, in globalization era information technology is advancing rapidly. Computers are equipment that was created to facilitate human work, currently achieving progress both in hardware and software. Kelurahan Sumur Batu requires an information system that supports and provides information services that are satisfying for information seekers. Kelurahan Sumur Batu is one of the smallest units of the DKI Jakarta Government which has an important role in conveying the vision and mission of the DKI Jakarta Government. The design of information systems is the best solution to solve the problem of lack of information for the people in Kelurahan Sumur Batu. With the existence of a web-based Government Information System, the information obtained will become more attractive, faster and easily accessible to many people.